STRATEGI KOMUNIKASI POLITIK (KAMPANYE) YANG DILAKUKAN OLEH PASANGAN CALON DRS. H. T. IRFAN TB DAN TGK. YUSRI JELANG PEMILIHAN UMUM KEPALA DAERAH TAHUN 2017 DI KABUPATEN ACEH JAYA - Aminah Aminah (SOURCE : Jurnal Ilmu Komunikasi, 2017)
This research aims to explain about political Communication Strategy (the campaign) what isdone by the success team and the couple Drs. H. T. Irfan TB and Tgk. Yusri so elected as aboutand proceeding from the in the district of Aceh Jaya 2017-2022 period. Data required in thisstudy was obtained through literature and field research. The research literature is done byreading textbooks, legislation, and other reading materials related to this research. While thefield research conducted by interviewing informants. The results of the study showed that thereare various strategies that done by the candidate pair Drs. H. T. Irfan TB and Tgk. Yusri. Nowthe political communication strategies that applied namely (1) makes the program hands outscholarships the son of Aceh Jaya smartphone continued as the vision and mission for the period2017-2022. (2) Running through the Aceh Party (3) Making the former GAM a successful team.(4) Establishment of successful sub-district and village level teams. (5) Good cooperation betweenparty bearers and supporting parties. (6) Quality of products offered at the time of the campaign.(7) Vehicles used in the conduct of the political marketing through advertising and campaigns.Keywords: Strategy, Political Communication and the ElectionA. Latar